The Givenness of Desire Human Subjectivity and the Natural Desire to See God - Rosenberg, Randall S. (Lonergan Studies, 2017)
This book examines the human desire for God through the lens of Bernard Lonergan's 'concrete subjectivity.' With Lonergan as an integrating thread, the author engages a variety of thinkers, including Hans Urs von Balthazar, Jean-Luc Marion, Rene Girard, Lawrence Feingold, John Milbank, John Paul II, Benedict XVI, Pope France, among others. The Givenness of Desire investigates our paradoxical desire for God that is rooted in in both the natural and supernatural.